A large-scale prospective study of big wins and their relationship with future involvement and risk among actual online sports bettors. (May 2023) - Edson, Timothy C.; Louderback, Eric R.; Tom, Matthew A.; Philander, Kahlil S.; Slabczynski, John M.; Lee, Taylor G.; LaPlante, Debi A.
Abstract: Clinicians have proposed that big wins early in a gambler's betting experience can lead to increased involvement, and eventually problematic gambling. Understanding how this effect manifests in online sports betting is important, as this form of gambling has grown increasingly popular worldwide and continues to expand. Methods: Using matched pair analysis and other methods (e.g., survival analysis, fixed effects regression), we examined big wins' ability to predict future gambling involvement and behavior using bet level data from 36, 328 sports gamblers who subscribed to a large, European online gambling operator. Big wins were defined two ways. Results: Big wins in sports betting were associated with increased engagement, losses, and risk in the following weeks, with the impact declining over time. The exact timing of when a big win occurs after subscribing does not appear to have a major effect on subsequent behaviors. These findings held for both definitions of big wins. Implications: This study supports the existence of a big win effect in online sports betting, but more research is needed to determine whether there is an "early" big win effect, and whether big wins are indeed associated with problematic gambling. Highlights: Clinicians suggest that subjectively large gambling wins ("big wins") can lead to excessive gambling involvement. This study represents the first longitudinal assessment of the big win effect using online sports gambling records. Big wins were associated with subsequently increased engagement, losses, and risk, however this effect declines over time. Sensitivity analyses showed that our main findings on big win effects were robust. Operators should alert gamblers about the importance of using responsible gambling strategies after a big win..